Pengaruh Pengendalian Internal dan Transparansi terhadap Kinerja Keuangan Nirlaba Masjid di Kota Jambi - Mufidah, Mufidah; Febrianti, Ira; Masnun, Masnun (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to analyze the influence of internal control and transparency of mosque fund management on the accountability of effective and efficient non-profit organization financial performance. The object of this study is the treasurer of a large mosque that has financial reports located on the main roads of Jambi City. The results of this study indicate that internal control has an effect on non-profit accountability and financial performance. Mosque accountability has an effect on the financial performance of non-profit mosque organizations, while transparency only has an effect on accountability and not financial performance.